Clinical and Radiological Correlation of Spinal Tuberculosis - Bashir Ahmed, Kauser Mahmood, Sanober Omer, Shehla Tanveer, Tooba Ali, Syeda Umm-E-Habiba, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The aim of this study is to establish a comprehensive understanding of the clinical and radiological features of spinal tuberculosis, and to evaluate their correlation in order to enhance diagnostic accuracy, management strategies, and patient outcomes. Study Design: This was a retrospective, observational, cross-sectional study. Place of Study: The research was conducted at the Department of Neuro-Sugery, Darul -Sehat Hospital and Neurology and Radiology Department of Creek General Hospital, both tertiary care hospital of Karachi. Duration of Study: Data were collected over a period of two years from January 2021 to December 2022. Methodology: A total of 120 patients diagnosed with spinal tuberculosis were included in this retrospective, observational, cross-sectional study.. Demographic data, clinical presentations, laboratory findings, and radiological findings were collected and analyzed. The radiological features were assessed using X-ray, computed tomography (CT), and magnetic resonance imaging (MRI) scans. Statistical analysis was performed to identify correlations between clinical and radiological findings and their associations with patient outcomes. Results: The mean age of patients was 46.3 years, with a slight male predominance. The most common clinical manifestations were back pain (89.3%), neurological deficits (57.3%), and constitutional symptoms (45.3%). The thoracic spine was predominantly affected (61.3%), followed by the lumbar (28%) and cervical regions (10.7%). Radiological findings demonstrated vertebral destruction (90.7%), disc space narrowing (83.3%), paravertebral abscesses (76%), and epidural involvement (58%). A strong correlation was observed between the severity of clinical manifestations and the extent of radiological abnormalities. Patients with extensive vertebral destruction and spinal cord compression showed significantly higher rates of neurological deficits. Conclusion: This study highlights the crucial role of clinical and radiological correlation in the diagnosis and management of spinal tuberculosis. Early recognition of the disease, prompt initiation of appropriate treatment, and regular monitoring of clinical and radiological progress can significantly improve patient outcomes and reduce long-term complications. Keywords: spinal tuberculosis, clinical features, radiological features, correlation, diagnosis, management, prognosis.